2020
DOI: 10.1136/bmjopen-2020-039369
|View full text |Cite
|
Sign up to set email alerts
|

Excess cases of influenza and the coronavirus epidemic in Catalonia: a time-series analysis of primary-care electronic medical records covering over 6 million people

Abstract: ObjectivesThere is uncertainty about when the first cases of COVID-19 appeared in Spain. We aimed to determine whether influenza diagnoses masked early COVID-19 cases and estimate numbers of undetected COVID-19 cases.DesignTime-series study of influenza and COVID-19 cases, 2010–2020.SettingPrimary care, Catalonia, Spain.ParticipantsPeople registered in primary-care practices, covering >6 million people and >85% of the population.Main outcome measuresWeekly new cases of influenza and COVID-19 clinically d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…Different from Italy, where infections were concentrated in the North [9], the combination of these repeated introductions with early, unnoticed community transmission resulted in consecutive outbreaks in distant, highly populated areas of the Basque Country and Navarra (North), Madrid (Centre), Catalonia (North East), Andalusia (South) and Valencia (East). This is supported by preliminary evidence for an excess of cases diagnosed as influenza during February and March in Catalonia, compared with the historical record, which probably masked early COVID-19 infections [11]. The spatial structure of the Spanish populations played a role in the rapid spread of the pandemic in some regions the country [see 12].…”
Section: Introductionmentioning
confidence: 82%
“…Different from Italy, where infections were concentrated in the North [9], the combination of these repeated introductions with early, unnoticed community transmission resulted in consecutive outbreaks in distant, highly populated areas of the Basque Country and Navarra (North), Madrid (Centre), Catalonia (North East), Andalusia (South) and Valencia (East). This is supported by preliminary evidence for an excess of cases diagnosed as influenza during February and March in Catalonia, compared with the historical record, which probably masked early COVID-19 infections [11]. The spatial structure of the Spanish populations played a role in the rapid spread of the pandemic in some regions the country [see 12].…”
Section: Introductionmentioning
confidence: 82%
“…The first case in Europe was reported on 20 January 2020 in France and the first case in Catalonia (Spain) was on 25 February 2020. However, some studies have suggested a previous circulation of the virus [8, 9]. Due to the rapid spread of the disease, on March 14 Spain established a national lockdown, as many other countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because some symptoms of COVID-19 and influenza are similar, 12 it has been suggested that influenza could mask early COVID-19 cases during the 2019–2020 season. 24 …”
Section: Discussionmentioning
confidence: 99%